2018
DOI: 10.1021/acsnano.8b00576
|View full text |Cite
|
Sign up to set email alerts
|

Highly Uniform Carbon Sheets with Orientation-Adjustable Ordered Mesopores

Abstract: A soft-hard template-assisted method toward the unconventional free-standing ordered mesoporous carbon sheets (OMCSs) with uniform hexagonal morphology is developed by applying MgAl-layered double hydroxide (MgAl-LDH) as the hard template, triblock copolymer F127 as the soft template, and phenolic resols as the carbon sources. It is found that the surface of MgAl-LDH can induce the morphology variation of resol-F127 monomicelles, leading to the formation of vertically or horizontally aligned mesopore arrays in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 60 publications
2
61
0
Order By: Relevance
“…It was found that the concentration of Co 2+ in the LDH laminates could greatly influence the growth of ZIF‐67 microcrystals and the final carbon‐based nanostructures. Similarly, Wu and co‐workers prepared ordered mesoporous carbon NSs by using LDHs as a surface‐confined nanoreactor 74. The surface of MgAl‐LDH plays a crucial role in tuning the orientation of mesopores in the carbon NSs, where vertically or horizontally aligned mesopores can be obtained.…”
Section: D Nanostructured Materials Based On Confined Synthesismentioning
confidence: 99%
“…It was found that the concentration of Co 2+ in the LDH laminates could greatly influence the growth of ZIF‐67 microcrystals and the final carbon‐based nanostructures. Similarly, Wu and co‐workers prepared ordered mesoporous carbon NSs by using LDHs as a surface‐confined nanoreactor 74. The surface of MgAl‐LDH plays a crucial role in tuning the orientation of mesopores in the carbon NSs, where vertically or horizontally aligned mesopores can be obtained.…”
Section: D Nanostructured Materials Based On Confined Synthesismentioning
confidence: 99%
“…For a long time in the past, the synthesis of pore‐controlled porous carbon materials resorted mainly to the template methods . And here, we abandoned the traditional methods and tried to make full use of the microstructure of the interpenetrating polymer networks to control the pore size.…”
Section: Resultsmentioning
confidence: 99%
“…For a long time in the past, the synthesis of pore-controlled porous carbon materials resorted mainly to the template methods. [22] And here, we abandoned the traditional methods and tried to make full use of the microstructure of the interpenetrating polymer networks to control the pore size. The synthetic route of microporous carbon material with uniform pore size and interconnected channel by the strategy of thermally decomposing MF/PAAS IPNs is as illustrated in Scheme 1A.…”
Section: Superiority Of Mf/paas Ipns As Carbon Precursors and Structumentioning
confidence: 99%
“…An abundant of mesopores/macropores and large ion‐accessible surface areas are attractive features of porous carbon materials for electrochemical energy storage . To verify this advantage of porous carbon materials, CV and galvanostatic charge–discharge (GCD) tests were carried out by the three‐electrode system in 6 m KOH.…”
Section: Resultsmentioning
confidence: 99%